The Effect of Competence and Compensation on Employee Performance with Job Stress as a Mediating Variable: A Study at Yayasan Badan Wakaf Al-Qur’an - Purinanta, Abi Sina; Wardhani, Nia Kusuma (IJOSMAS, 2025)
This research addresses the decline of public trust in philanthropic institutions in Indonesia after the misuse of donation funds in 2022. The case affected the Yayasan Badan Wakaf Al-Qur’an, which faced a decrease in donation revenue in 2023. The organization conducted an internal evaluation, and the researcher examined employee performance through competence, compensation, and job stress. The purpose of this study is to analyze the effect of competence and compensation on employee performance with job stress as a mediating variable. The researcher conducted this study in 2024 on 150 employees of Yayasan Badan Wakaf Al-Qur’an. The sample consisted of 110 employees who were selected using the Slovin formula. The researcher applied a quantitative method with a causal associative approach. The researcher collected primary data through online questionnaires and analyzed the data using Structural Equation Modeling (SEM) in SmartPLS4. The findings show that competence significantly improves employee performance and reduces job stress. Compensation does not influence job stress and does not influence employee performance. Job stress significantly decreases employee performance. Competence indirectly improves employee performance through job stress, but compensation does not show any indirect effect. These results highlight the importance of strengthening competence to improve employee performance in nonprofit organizations.